A New Model Trypanosomatid, Novymonas esmeraldas: Genomic Perception of Its "Candidatus Pandoraea novymonadis" Endosymbiont - Zakharova, Alexandra; Saura, Andreu; Butenko, Anzhelika; Podešvová, Lucie; Warmusová, Sandra; Kostygov, Alexei Yu; Nenarokova, Anna; Lukeš, Julius; Opperdoes, Fred R; Yurchenko, Vyacheslav (mBio, 2021)
The closest relative of human pathogen Leishmania, the trypanosomatid Novymonas esmeraldas, harbors a bacterial endosymbiont "Candidatus Pandoraea novymonadis." Based on genomic data, we performed a detailed characterization of the metabolic interactions of both partners. While in many respects the metabolism of N. esmeraldas resembles that of other Leishmaniinae, the endosymbiont provides the trypanosomatid with heme, essential amino acids, purines, some coenzymes, and vitamins. In return, N. esmeraldas shares with the bacterium several nonessential amino acids and phospholipids. Moreover, it complements its carbohydrate metabolism and urea cycle with enzymes missing from the "Ca. Pandoraea novymonadis" genome. The removal of the endosymbiont from N. esmeraldas results in a significant reduction of the overall translation rate, reduced expression of genes involved in lipid metabolism and mitochondrial respiratory activity, and downregulation of several aminoacyl-tRNA synthetases, enzymes involved in the synthesis of some amino acids, as well as proteins associated with autophagy. At the same time, the genes responsible for protection against reactive oxygen species and DNA repair become significantly upregulated in the aposymbiotic strain of this trypanosomatid. By knocking out a component of its flagellum, we turned N. esmeraldas into a new model trypanosomatid that is amenable to genetic manipulation using both conventional and CRISPR-Cas9-mediated approaches. IMPORTANCENovymonas esmeraldas is a parasitic flagellate of the family Trypanosomatidae representing the closest insect-restricted relative of the human pathogen Leishmania. It bears symbiotic bacteria in its cytoplasm, the relationship with which has been established relatively recently and independently from other known endosymbioses in protists. Here, using the genome analysis and comparison of transcriptomic profiles of N. esmeraldas with and without the endosymbionts, we describe a uniquely complex cooperation between both partners on the biochemical level. We demonstrate that the removal of bacteria leads to a decelerated growth of N. esmeraldas, substantial suppression of many metabolic pathways, and increased oxidative stress. Our success with the genetic transformation of this flagellate makes it a new model trypanosomatid species that can be used for the dissection of mechanisms underlying the symbiotic relationships between protists and bacteria.
Keywords: Symbiosis; genom bakteriální; Trypanosomatidae; genomics; genomika; bacterial endosymbiont; metabolism; Bacteria; Genome, Bacterial; Leishmaniinae; Genomics; symbióza; Phylogeny; fylogeneze; Trypanosoma